DRUG ADVERTISING: CONSOLIDATION OF HYPOCHONDRIA IN BRAZIL - Norberto Ribeiro Soares, Filipe (Revista Gênero e Interdisciplinaridade, 2023)
The present study aims to establish a relationship between drug advertising and the practice of self-medication, as well as the characterization of individuals as hypochondriacs due to the discourse of drug advertisements. Mainly driven by financial reward, the industries in the field are not always guided by medical ethics and commitment to public health.